Untargeted metabolite profiling of Philippine-grown crescentia cujete and its commercial fruit juice using GC-MS and UPLC-HRMS - Rellin, Klidel Fae B.; Dasmarinas, Dianne D.; Junio, Hiyas A. (2018)
Calabash fruit (Crescentia cujete L.) juice has gained traction in Southern Philippines for its miraculous effect against stroke, diabetes, and cancer. Metabolite profile of local C. cujete fruit pulp and the commercial fruit juice were established using gas chromatography mass spectrometry (GC-MS) and ultra-high perfromance liquid chromatography high-resolution mass spectrometry (UPLC-HRMS). Putative hits to the NIST Mass Spectral Library included methyl salicylate, (+)-δ-cadinene, benzene and its derivatives such as toluene and o-xylene. Toluene and o-xylene are known air pollutants. Results indicated that the fruit has the potential to bioaccumulate small organic molecules. Volatile organic compounds detected in the fruit pulp were absent from the processed commercial juice. Other benzenoid compounds ? thiazole and (+)-δ-cadinene, which are important biosynthetic precursors ? were identified from the juice sample. Molecular networking analysis of the tandem MS data of the ethanol extract of the juice putatively identified the presence of 1-kestose and sucrose. 1-Kestose is considered as an essential prebiotic compound associated with boosting metabolism and immunity. Other kestose isomers were also indicated to be present in the juice based on the elution profile and MS/MS data. Preliminary activity tested for both samples yielded positive result against Candida albicans using disc diffusion asay. Only the juice sample yielded significant activity against Escherichia coli.